The role of technological innovation and institutional quality in environmental and economic growth sustainability in emerging Asian countries - Zhang, Ruiyue; Jing, Liu; Li, Yutong; Guo, Xu (Frontiers in Environmental Science, 2025)
Economic activities based on primary industrial operations and fossil fuel energy cause environmental pollution by releasing carbon dioxide that is harmful to the environment. Green technological innovation and institutional quality are considered important tools to reduce environmental emission levels and promote economic growth. However, there are few studies that explore the role of technological innovation and institutional quality in exacerbating environmental pollution from the perspective of emerging Asian countries. Thus, this study unveils the influence of green technology innovation, institutional quality, renewable energy use and non-renewable energy use on per capita carbon emissions and per capita economic growth in emerging Asian countries from 1995 to 2022. The current study uses second-generation augmented mean group and common correlated effects mean group panel methods, taking into account residual cross-sectional dependence and heterogeneity to reveal long term relationship between dynamics. The analysis results emphasize that every 1% expansion of technological innovation can strongly reduce per capita carbon dioxide emissions by 0.329%, while effectively boosting per capita economic growth by 0.397%. However, every 1% improvement in institutional quality can effectively promote per capita carbon dioxide emissions and per capita economic growth by 0.243% and 0.362% respectively. Moreover, renewable energy strongly reduces environmental emissions and promotes economic enhancement, while non-renewable energy considerably stimulates environmental pollution and economic progress. Based on the revealed exploration, this study recommends that emerging markets in Asia should strengthen their respective institutional quality to focus on investing in green technology innovation and renewable energy projects to achieve sustainable development goals.